Multiple response optimization of Bacillus subtilis EA-CB0015 culture and identification of antifungal metabolites (2014)
The low yields of biomass and antimicrobial metabolites obtained in fermentation processes are limiting factors for implementing biological control agents in the field -- In this context, optimization of the culture medium for the biological control agent Bacillus subtilis EA-CB0015 was conducted in submerged culture to maximize the biomass production and antifungal activity -- Additionally, the active metabolites against the phytopathogen Mycosphaerella fijiensis produced under optimized conditions were identified -- Carbon and nitrogen constituents of the culture medium were optimized using a 22 factorial design with central point followed by a multiple response optimization coupled to the desirability function approach -- The optimized medium (33.4 g/L of glucose and 32.5 g/L of yeast extract), showed significant increases in both, cell density by 3.6 folds (13.271.0 g/L) and antifungal activity by 1.2 folds (77.770.3% inhibition) -- To gain insight into the type of active compounds, they were purified and identified by mass spectrometry (MS) -- The MS analysis revealed the presence of three families of lipopeptides: surfactin, fengycin and iturin -- The high antifungal activity was associated with the novel fengycin C and with iturin -- A which were partially growth-associated with a maximum concentration of 781.4 and 355.4 mg/L at 36 h of growth, respectively -- These results indicate the potential of B. subtilis EA-CB0015 to produce high concentrations of biomass and lipopeptides that can be exploited for biotechnological application